Upaya Peningkatan Prestasi Belajar Siswa Kelas VII C SMP Negeri 1 Cawas, Klaten Melalui Metode CTL Pada Materi Konsep Organisasi Kehidupan Tahun Pelajaran 2016/2017 - Jawa Tengah, Qohdari Guru SMP Negeri 1 Cawas Klaten (Teknis, 2017)
Improving the quality of education in schools was directly related to the students as learners and teachers as educators, and it could be seen from the performance of students learning. In an effort to improve student performance at SMP Negeri 1 Cawas, there are students who are less enthusiastic in learning and student performance still does not appear as expected. To improve student performance at SMP Negeri 1 Cawas, CTL learning methods (Contextual Teaching and Learning) could be implemented. This research aimed to describe the efforts of educators in implementing the CTL method to improve student learning performance in the learning material concept of life organization in class VII C SMP Negeri 1 Cawas academic year 2016/2017. The research was conducted in class VII C SMP Negeri 1 Cawas with 32 students, from June until December 2013. The focus of this research was the application of CTL method in learning material of life organization concept. Class Action Research used two cycles. Each cycle consisted of four steps i.e planning, action, observation and reflection. Once itâs done, then proceeded to discussion and conclusion drawing. The results of this research showed an increase in studentâs performance, as seen in observed indicators of average scores of studentâs learning test and percentage of completeness , proved by the scores obtained from the initial conditions, cycle I, and cycle IIÂ  has increased significantly. The average scores has increased from 59,37 to 79,53. On the other hand, the percentage of completeness has increased from 15,62% to 90,62%. Use of CTL method can helps teacher improving student performance, particularly in learning. This learning process requires teachers to be more active in class once the materials given to the students. This method also able to minimize the difficulties often faced by teachers in the learning process. As suggestions, teacher need to be more creative and innovative in creating variation of learning methods. Teachers are also need to be more actively involved, to enable the synergies between implemented learning methods with the quality of student output.Keyword : Learning Performance, CTL method, Material of Life Organization Concept.